Sulphur fertilization influences the sulphur species composition in Allium sativum: sulphomics using HPLC-ICPMS/MS-ESI-MS/MS. Issue 10 (21st September 2017) - Raab, Andrea; Ronzan, Marilena; Feldmann, Joerg
Abstract : Comprehensive non-target analysis identifies 54 sulphur containing compounds in garlic. Abstract : Garlic ( A. sativum ) contains a large number of small sulphur (S)-containing metabolites, which are important for its taste and smell and vary with A. sativum variety and growth conditions. This study was designed to investigate the influence of different sulphur-fertilization regimes on low molecular weight S-species by attempting the first sulphur mass balance in A. sativum roots and bulbs using HPLC-ICPMS/MS-ESI-MS/MS. Species unspecific quantification of acid soluble S-containing metabolites was achieved using HPLC-ICP-MS/MS. For identification of the compounds, high resolution ESI-MS (Orbitrap LTQ and q-TOF) was used. The plants contained up to 54 separated sulphur-containing compounds, which constitute about 80% of the total sulphur present in A. sativum . The roots and bulbs of A. sativum contained the same compounds, but not necessarily the same amounts and proportions. The S-containing metabolites in the roots reacted more sensitively to manipulations of sulphur fertilization than those compounds in the bulbs. In addition to known compounds ( e.g. γ-glutamyl- S -1-propenylcysteine) we were able to identify and partially quantify 31 compounds. Three as yet undescribed S-containing compounds were also identified and quantified for the first time. Putative structures were assigned to the oxidised forms of S -1-propenylmercaptoglutathione, S -2-propenylmercaptoglutathione, S -allyl/propenyl-containing PC-2 and 2-amino-3-[(2-carboxypropyl)sulfanyl]propanoic acid. The parallel use of ICP-MS/MS as a sulphur-specific detector and ESI-MS as a molecular detector simplifies the identification and quantification of sulphur containing metabolites without species specific standards. This non-target analysis approach enables a mass balance approach and identifies the occurrence of the so far unidentified organosulphur compounds. The experiments showed that the sulphur-fertilization regime does not influence sulphur-speciation, but the concentration of some S-containing compounds in roots is dependent on sulphur fertilization.